The Tomato BLADE ON PETIOLE and TERMINATING FLOWER Regulate Leaf Axil Patterning Along the Proximal-Distal Axes - Izhaki, Anat; Alvarez, John P.; Cinnamon, Yuval; Genin, Olga; Liberman-Aloni, Raya; Eyal, Yoram (Frontiers in Plant Science, 2018)
Leaf axil patterning occurs concomitantly with leaf development and takes place at the boundary zone which demarcates the initiating leaf primordium from the shoot apical meristem. Subsequent growth and differentiation result in establishment of the axillary meristem and abscission zone (AZ) along the proximal-distal axis of the leaf axil, yet the molecular mechanisms that regulate these events are poorly understood. We studied the role of the tomato BLADE ON PETIOLE (SlBOP) boundary gene family on the development of the leaf axil using BOP-silenced plants as well as BOP-mutated lines. We show that silencing of the tomato SlBOP gene family affects patterning of the leaf axil along the proximal-distal axis, manifested by dispositioning of the AM and abnormal development of the adjacent tissue resulting in lack of a functional leaf AZ. Dissection of the role of each of the three tomato SlBOPs by analysis of single, double and triple null-mutants demonstrated that SlBOP2 is the dominant gene in leaf axil patterning, but does not rule out involvement of SlBOP1 and SlBOP3 in correct AM positioning. We further studied the potential role of TERMINATING FLOWER (TMF), a transcription factor which was previously shown to interact with SlBOPs, in leaf axil patterning using TMF mutant tomato lines. The results suggest that similar to SlBOP2, TMF is involved in leaf axil proximal-distal patterning and AZ development.